Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.151
|View full text |Cite
|
Sign up to set email alerts
|

Value-In-Context with Service Innovation in the Digital Age: A Service-Dominant Logic Perspective

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Source: Authors Quality of business organization: Research has been identified as one of the most crucial drivers of business development. Companies invest in research directly by creating knowledge and by adapting existing innovations to their industry (Cohen & Levinthal, 1990;Mikusz, 2017;Raymond, Bergeron, Croteau & St-Pierre, 2016). The impact of dynamic technological progress requires regular enhancement of the company's BM to sustain positive financial outcomes (Linder & Cantrell 2001).…”
Section: Digital Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Source: Authors Quality of business organization: Research has been identified as one of the most crucial drivers of business development. Companies invest in research directly by creating knowledge and by adapting existing innovations to their industry (Cohen & Levinthal, 1990;Mikusz, 2017;Raymond, Bergeron, Croteau & St-Pierre, 2016). The impact of dynamic technological progress requires regular enhancement of the company's BM to sustain positive financial outcomes (Linder & Cantrell 2001).…”
Section: Digital Datamentioning
confidence: 99%
“…The innovative approach to market expansion no longer supports traditional market segmentation methods, the main attributes of which are the product and the customer, but focuses on the conditions in which customers are located rather than on the customers themselves (Hackos, 2003) and on the benefits as a final result (Hackos, 2003;Mikusz, 2017). This approach proposes the design of a new business model based on a service-dominated approach (Ekundayo, 2019;Fullerton & Wempe, 2009;Hackos, 2003;Kotarba, 2018;Linder & Cantrell 2001;Malmmose, Lueg, Khusainova, Iversen, & Panti, 2015;Mikusz, 2017;Viljakainen, Toivonen & Aikala, 2013).…”
Section: Digital Datamentioning
confidence: 99%
See 3 more Smart Citations